The dynamic changes of mango (Mangifera indica L.) epicuticular wax during fruit development and effect of epicuticular wax on Colletotrichum gloeosporioides invasion - Wu, Jingbo; You, Yuquan; Wu, Xiao; Liu, Feng; Li, Guoping; Yin, Hao; Gu, Chao; Qi, Kaijie; Wei, Qing; Wang, Songbiao; Yao, Quansheng; Zhan, Rulin; et al. (Frontiers in Plant Science, 2023)
Mango fruits are susceptible to diseases, such as anthracnose, during fruit development, leading to yield reduction. Epicuticular wax is closely related to resistance of plants to pathogenic bacterial invasion. In this study, the effect of mango epicuticular wax on the invasion of Colletotrichum gloeosporioides was investigated, followed by the identification of the chemical composition and crystal morphology of the mango epicuticular wax at five developmental periods. Results showed that the epicuticular wax of mango fruits can prevent the invasion of C. gloeosporioides, and 'Renong' showed the strongest resistance to C. gloeosporioides. The wax content of four mango varieties first increased and then decreased from 40 days after full bloom (DAFB) to 120 DAFB. In addition, 95 compounds were detected in the epicuticular wax of the four mango varieties at five developmental periods. Primary alcohols, terpenoids, and esters are the main compounds found in the epicuticular wax of mango throughout development. Furthermore, the surface wax structure of mango fruit changed dynamically during fruit development, and irregular platelet-like crystals were the main wax structure. These results provide a reference for the follow-up study of mango fruit epidermal wax synthesis mechanism and breeding.